The structure of municipal council committees of local governments of Hungary before and after the local elections of 2014 - Marincsák, Mariann; Kozma, Gábor; Pénzes, János (Univerzita Pardubice, 2016)
The aim of the present paper is examine the committee structure of municipal councils of Hungarian settlements having a population over 5,000 before and after the local elections of 2014, and to analyse the presence of external experts in the work of the various committees. The most important findings can be summarized as follows: the average number of municipal council committees shows a strong correlation with the size of the settlements. The roles of the individual sectors as filled in the municipal council committees, and the changes to the same, are affected by amendments in the relevant laws and the subsequent governmental measures. The participation of external members in the municipal council committees is typical primarily in sectors that are less important and require mainly professional knowledge; at the same time, municipal councils strive to keep external members away from the work of committees discussing issues that are confidential or otherwise sensitive from the point of view of the local governments.
Keywords: municipal council committees; Hungary; size of settlements; democratism; local election of 2014; H75; H76; Z18